The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/s41598-017-13639-y
|View full text |Cite|
|
Sign up to set email alerts
|

A Pilot Study on Tocilizumab for Treating Refractory Adult-Onset Still’s Disease

Abstract: To investigate the efficacy and safety of Tocilizumab (TCZ) in patients with refractory adult-onset Still’s disease (AOSD). We enrolled 8 female patients from October 2013 to July 2014. All patients fulfilled Japan’s Yamaguch AOSD classification and recognized as refractory AOSD. All Patients received TCZ treatment 4–8 mg/kg every 4 weeks. Evaluation of efficacy was conducted after 3 months and 6 months, including clinical manifestations of AOSD patients, improvement of inflammatory markers as well as glucocor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…It is characterized by elevated levels of inflammatory cytokines in serum including IL-6, IL-18, IL-1, TNFα and IFNγ. An increasing number of case reports or series has shown the effectiveness of TCZ on AOSD and reduction of glucocorticoid dose [ 117 , 118 , 119 ]. A meta-analysis of 10 studies with 147 patients showed that TCZ therapy achieved a partial remission rate in 85.38% and complete remission rate in 77.91%, and even in patients with refractory cases, the remission rate was 87.92% [ 120 ], suggesting a promising effect of TCZ on AOSD.…”
Section: Therapeutic Targeting Of Il-6 In Diseasesmentioning
confidence: 99%
“…It is characterized by elevated levels of inflammatory cytokines in serum including IL-6, IL-18, IL-1, TNFα and IFNγ. An increasing number of case reports or series has shown the effectiveness of TCZ on AOSD and reduction of glucocorticoid dose [ 117 , 118 , 119 ]. A meta-analysis of 10 studies with 147 patients showed that TCZ therapy achieved a partial remission rate in 85.38% and complete remission rate in 77.91%, and even in patients with refractory cases, the remission rate was 87.92% [ 120 ], suggesting a promising effect of TCZ on AOSD.…”
Section: Therapeutic Targeting Of Il-6 In Diseasesmentioning
confidence: 99%
“…In our study, we aim to describe, to our knowledge for the first time, the efficacy of tofacitinib in 14 patients with refractory AOSD. All patients fulfilled Yamaguchi’s criteria and were classified as refractory AOSD as defined previously 6. They were followed up for the shortest of 1 month and the longest for 24 months by the same medical team.…”
mentioning
confidence: 99%
“…Karmakar et al reported that IL-17 promoted bone erosion in a murine collagen-induced arthritis model by upregulating the expression of RANKL and RANK, thereby enhancing osteoclastogenesis [ 11 ]. Li et al recently found that the IL-6 receptor monoclonal antibody, tocilizumab, exerted a favorable effect on recurrent AOSD [ 12 ]. These findings suggest that the RANK/RANKL pathway represents a pathogenic mechanism of bone erosion and/or destruction in arthritic diseases, including AOSD.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the RANK/RANKL pathway represents a pathogenic mechanism of bone erosion and/or destruction in arthritic diseases, including AOSD. We and others have found denosumab to be useful for GIO patients [ 8 , 12 , 13 , 14 , 15 ]. Although BPs are first-line drugs for GIO, the current patients exhibited upper gastrointestinal issues that precluded BP use.…”
Section: Discussionmentioning
confidence: 99%